Pengaruh WEB-SEREIS (Website Sistem Informasi Edukasi Aksi Pencegahan Diabetes Millitus) Terhadap Pengetahuan Dan Perilaku Pencegahan Diebetes Millitus Tipe 2 Pada RemaEB - Novita Surya Putri; Tria Anisa Firmanti; Annisa Nur Nazmi (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:   DM is a current trend caused by changes in physical activity (sports), stress, work environment, diet and lifestyle. The current lifestyle is predicted to be dangerous for diabetes, especially in adolescents. The purpose of this study was to determine the effect of WEB-SEREIS (Website Education Information System for Diabetes Millitus Prevention Action) on the knowledge and behavior of preventing type 2 diabetes mellitus in adolescents.Methods:  This research is a quasi-experimental research with a pre-test and post-test only control group design approach. Sampling used in this study using purposive sampling. The sample in this study were adolescents consisting of 2 sample groups, namely the intervention group and the control group, each of which was 53 respondents. Data collection Diabetes Knowledge Questionnaire 24 (DKQ24), Global Physical Activity Questionnaire (GPAQ) from WHO, Depression Anxiety Stress Scales. Inferential analysis using Wilcoxon p-value < 0.05.Results:   Knowledge and prevention behavior of Type 2 Diabetes Mellitus in adolescents with WEB-SEREIS intervention showed that there was a significant difference between the intervention group and the control group with a p-value of knowledge of 0.024 (˂ 0.05), physical activity 0.000 (˂ 0.05), depression 0.000 (˂ 0.05), anxiety 0.014 (˂ 0.05), stress 0.001 (˂ 0.05), and GDS 0.002 (˂ 0.05).Conclusion: WEB-SEREIS is an embodiment of health education for adolescents by utilizing appropriate technology with fast access and sources of information based on empirical evidence to have a positive impact on adolescent health through increasing knowledge and changing good behavior